Effects of Whole Body Therapeutic Hypothermia on Gastrointestinal Morbidity and Feeding Tolerance in Infants with Hypoxic Ischemic Encephalopathy. (25th August 2014) - Thornton, Kimberly M.; Dai, Hongying; Septer, Seth; Petrikin, Joshua E.
Abstract : Objective . This retrospective cohort study evaluated the effects of whole body therapeutic hypothermia (WBTH) on gastrointestinal (GI) morbidity and feeding tolerance in infants with moderate-to-severe hypoxic ischemic encephalopathy (HIE). Study Design . Infants ≥ 35 weeks gestational age and ≥1800 grams birth weight with moderate-to-severe HIE treated from 2000 to 2012 were compared. 68 patients had documented strictly defined criteria for WBTH: 32 historical control patients did not receive WBTH (non-WBTH) and 36 cohort patients received WBTH. Result . More of the non-WBTH group infants never initiated enteral feeds (28% versus 6%; P = 0.02 ), never reached full enteral feeds (38% versus 6%, P = 0.002 ), and never reached full oral feeds (56% versus 19%, P = 0.002 ). Survival analyses demonstrated that the WBTH group reached full enteral feeds (median time: 11 versus 9 days; P = 0.02 ) and full oral feeds (median time: 19 versus 10 days; P = 0.01 ) sooner. The non-WBTH group had higher combined outcomes of death and gastric tube placement (47% versus 11%; P = 0.001 ) and death and gavage feeds at discharge (44% versus 11%; P = 0.005 ). Conclusion . WBTH may have beneficial effects on GI morbidity and feeding tolerance for infants with moderate-to-severe HIE.